Direct Allylation of In Situ Generated Aldehyde Acyl Anions by Synergistic NHC and Palladium Catalysis1. Issue 27 (21st May 2014) - Ahire, Milind M.; Mhaske, Santosh B.
Abstract The direct regioselective allylation of in situ generated aldehyde acyl anions has been achieved by synergistic NHC and Pd catalysis. It provides an efficient access to valuable β, γ‐unsaturated ketones under mild reaction conditions starting from easily accessible allylic carbonates and aldehydes without any preactivation. The synergistic catalysis method demonstrated herein adds a new dimension to the area of metal‐mediated C allylation.